Improving uncertainty tolerance in medical students: A scoping review. Issue 12 (18th July 2022) - Patel, Priya; Hancock, Jason; Rogers, Morwenna; Pollard, Samuel R.
Abstract: Introduction: Uncertainty is an inevitable part of medical practice. An ability to tolerate uncertainty is viewed as a key competency across many health‐care systems. Poor uncertainty tolerance (UT) has been linked to negative outcomes including reduced psychological well‐being in medical students. A variety of medical education interventions have been developed with the intention of increasing medical students' UT. However, there is no synthesis of these studies available to inform education and research practice. Our aim was to conduct a scoping review of medical education interventions that evaluate their impact on UT. Methods: Medline, PsycInfo, Embase and ERIC databases were searched for articles published from inception to December 2020. An extensive supplementary search was conducted and both quantitative and qualitative evaluations were included. For each intervention, we categorised the stimulus of uncertainty (ambiguity, complexity and/or probability) and mapped the students' reported cognitive, behavioural, and/or emotional response(s) to uncertainty onto an existing conceptual framework. Results: Twenty‐two of 24 included studies reported a positive impact on medical student UT in at least one domain (cognitive, behavioural or emotional). Interventions included problem based learning‐based curricula, medical humanities, simulation, reflection and assessment. We found in four studies that a negative response in the emotional domain was reported despite positive responses also being reported in the cognitive and/or behavioural domains. Conclusion: We identified a range of medical education interventions which report a positive impact on medical student UT. Further research is required to understand why a single intervention may stimulate a negative emotional response alongside a positive cognitive or behavioural response. In turn, this could support stakeholders such as policymakers and institutions to adapt the medical curriculum to better prepare their medical students for practice by enhancing their UT. Abstract : How can we improve medical students' uncertainty tolerance? This important question is addressed in the current issue through a review of existing interventions.